A Methods engineering study on High Ace Aluminum and Glass, Inc. - Lagunay, Novis; Ricalde, Rebecca R.; Venida, Venice A.; Viniegra, Mia Karmina (College of Engineering, 2001)
One of the business services that High Ace Aluminum and Glass, Inc. renders is aluminum recycling, and its monthly output averages abot 300 tons of recycled aluminum ingots. The whole production system of the company was documented. By using the tools and techniques learned in methods engineering, problems were identified concerning the manufacturing process. It was verified that material loss was the main problem, and its root causes were : inappropriate materials handling equipment, inappropriate storage equipment, and inefficient plant layout. Several alternatives were generated to alleviate the problem that is caused by inappropriate materials handling and storage equipment. An alternative to the inefficient facility layout was to propose a new design. This alternative stemmed from the idea of the owner of High Ace Aluminum and Glass, Inc. to relocate the plant to a new site. The alternatives were carefully weighed and evaluated according to their costs and benefits. These chosen alternatives would certainly alleviate not only the problem on material loss but also on other several problems that were not verified for any corrective actions.